PENGARUH JOB DEMANDS-RESOURCES TERHADAP ADAPTIVE PERFORMANCE: JOB CRAFTING SEBAGAI MEDIATOR PADA PEKERJA TELEKOMUNIKASI - Nadia Ayu Safira; Yus Nugraha; Anissa Lestari Kadiyono; Husnita Husnita (Universitas Muhammadiyah Lampung, 2026)
Organizational change is company's strategic response to increase business efficiency and effectiveness. PT. X as a cellular telecommunications company is undergoing process of change by launching Fixed Mobile Convergence (FMC) services through the acquisition of fixed internet services from its parent company. This process requires employees to adapt quickly. This study aims to determine the effect of job demands-resources (JD-R) on adaptive performance through job crafting on PT. X employees in West Java Region. The quantitative method used is General Linear Mediation Method (GLMM) through JAMOVI application. The study sample consisted of 105 employees using simple random sampling. The results showed that job crafting did not mediate the effect of job demands on adaptive performance (Beta= -0.0406, p > .001), but fully mediated the effect of job resources on adaptive performance (Beta= 0.2804, p < .001). The novelty of this study is explaining the mechanism of JD-R on adaptive performance through job crafting in the telecommunications context that is still limited. Theoretically, this study confirms the role of job resources in encouraging self-adjustment that improves adaptive performance, while practically PT. X Regional West Java needs to optimize job resources to support change.